2016
DOI: 10.1055/s-0042-105517
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Use of High-Intensity Focused Ultrasound (HIFU) for Tumor and Pain Reduction in Advanced Pancreatic Cancer

Abstract: Purpose: Evaluation of ultrasound-guided high-intensity focused ultrasound (HIFU) used for the first time in Germany in patients with inoperable pancreatic cancer for reduction of tumor volume and relief of tumor-associated pain. Materials and Methods: 15 patients with locally advanced inoperable pancreatic cancer and tumor-related pain symptoms were treated by HIFU (n?=?6 UICC stage III, n?=?9 UICC stage IV). 13 patients underwent simultaneous standard chemotherapy. Ablation was performed using the JC HIFU s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
1
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 13 publications
2
30
1
4
Order By: Relevance
“…It was first reported in 2000 that HIFU successfully ablates and treats pancreatic cancer (29). Several studies have confirmed the safety and efficacy of HIFU in the treatment of pancreatic cancer (10,(14)(15)(16)(19)(20)(21)(22)(23)(24)(25)(29)(30)(31)(32)(33)(34). The most common complications observed following HIFU treatment of pancreatic cancer include skin burns (10,15,17,(21)(22)(23)(30)(31)(32), pancreatitis (10,18,23,31,32), duodenal fistula (23,31) and obstructive jaundice (19,34).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was first reported in 2000 that HIFU successfully ablates and treats pancreatic cancer (29). Several studies have confirmed the safety and efficacy of HIFU in the treatment of pancreatic cancer (10,(14)(15)(16)(19)(20)(21)(22)(23)(24)(25)(29)(30)(31)(32)(33)(34). The most common complications observed following HIFU treatment of pancreatic cancer include skin burns (10,15,17,(21)(22)(23)(30)(31)(32), pancreatitis (10,18,23,31,32), duodenal fistula (23,31) and obstructive jaundice (19,34).…”
Section: Discussionmentioning
confidence: 99%
“…widely used in the treatment of uterine fibroids and hepatocellular carcinoma, with good therapeutic results (12). Previous studies have confirmed that HIFU therapy effectively alleviates cancer-associated abdominal pain, reduces tumor volume and may confer an additional survival benefit (11,(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). However, vascular complications caused by this treatment have been reported, including secondary occlusion of the superior mesenteric artery (24) and portal vein thrombosis (25).…”
Section: Effects Of High-intensity Focused Ultrasound Treatment On Pementioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the curative aspect of the procedure, HIFU has also been shown to have palliative importance by reducing tumor‐related pain and thus improving quality of life for patients with advanced disease. A large series with more than 200 patients with pancreatic cancer treated in China with HIFU suggested a reduction of the tumor size, reduction of visceral pain, and increased survival . There was a small percentage of in‐hospital complications, and no deaths were observed.…”
Section: Discussionmentioning
confidence: 99%
“…Interventionalisten abhängig sind. Der Ultraschall (US) ge steuerte HIFU bietet dabei eine minimalinvasive und wirksame Be handlungsoption, die in Kombination mit einer palliativen Stan dardchemotherapie zur Schmerzlinderung und lokalen Tumorkon trolle erfolgreich eingesetzt werden kann [7,8] und im Gegensatz zu den anderen lokal ablativen Verfahren ohne das Einbringen von Nadeln, Sonden oder Elektroden funktioniert. Vor diesem Hinter grund werden im Folgenden unsere Erfahrungen zur symptomati schen Therapie mit USgesteuertem HIFU beim fortgeschrittenen Pankreaskarzinom anderen lokal ablativen Verfahren gegenüber gestellt.…”
Section: Introductionunclassified